0
$\begingroup$

There is an object moving in circle, with this law:

$$ \alpha = -k^2 \theta $$

With $ \alpha = \frac{ d \omega }{dt} $, and $ \omega= \frac{d \theta}{dt} $, $\theta$ = angle, $k$ positive constant.

I need to compute $ \theta $ in function of time. My attempt:

$$ \frac{d^2 \theta}{dt^2} = -k \theta $$ $$ \frac{d^2 \theta}{\theta} = -k^2 dt^2 $$ $$ \int_{\theta_0}^{\theta} {\frac{d^2 \theta}{\theta}} = - \int{k^2 dt^2} $$ $$ \ln\Big(\frac{\theta}{\theta_0}\Big) d\theta = -k^2 t \cdot dt$$

So I try to get the solution computing:

$$ \int_{\theta_0}^{\theta} \ln\Big(\frac{\theta}{\theta_0}\Big) d\theta = -\int k^2 t \cdot dt $$

But it's wrong, the solution is $\theta = \theta_0 \sin \big( kt + \phi \big) $.

$\endgroup$
3
  • $\begingroup$ You face a standard differential equation, which is $y'' +\omega^2 y =0$. If $\omega \in \mathbb{R}$ then one way to write the general solution of this equation is $y(t) = \lambda \sin(\omega t + \phi)$ where $\lambda$ and $\phi$ are two constants that depends on initial conditions. You can check it yourself since you only need to derive $y(t)$ two times. But the way you started seems a bit complicated to me, the equation you're resolving is to simple to do that. $\endgroup$ – ChocoPouce Apr 17 '14 at 13:23
  • $\begingroup$ But $ \theta_0 \sin \big( kt + \phi \big) $ derived two times is $ - \theta_0 k^2 \sin \big( kt + \phi \big) $, not $-k^2 \theta$. $\endgroup$ – Ramy Al Zuhouri Apr 17 '14 at 13:45
  • $\begingroup$ Since $\theta = \theta_0 \sin(kt+\phi)$ I think you are ok. $\endgroup$ – ChocoPouce Apr 17 '14 at 13:48
1
$\begingroup$

The equation is a second-order linear differential equation; in standard form,

$$\frac{\mathrm{d}^2 \theta(t)}{\mathrm{d}t^2} + k^2\theta = 0$$

For the case of constant coefficients, one must simply propose the ansatz $\theta(t)=e^{Rt}$, where $R$ is a constant. Plugging into the differential equation yields,

$$e^{Rt}(R^2+k^2) = 0$$

This is only the case when $R^2+k^2=0$, which has solutions $R=\pm i k$. Using Euler's formula, we can express the two solutions of the differential equation as,

$$\theta_1 = \cos(kt) + i\sin(kt), \, \, \, \, \theta_2 = \cos(kt) - i\sin(kt)$$

However, recall the superposition principle applies to this differential equation, and hence any linear combination of these solutions is also a solution. We construct the following new solutions:

$$\Theta_1 = \frac{1}{2}(\theta_1 + \theta_2) = \cos(kt)$$ $$\Theta_2 = \frac{1}{2i}(\theta_1-\theta_2) = \sin(kt)$$

We can once again combine these solutions, and introduce two arbitrary constants (determined by initial conditions) to propose the general solution,

$$\theta(t) = c_1 \cos(kt) + c_2\sin(kt)$$

The equation is well-known, and that of a classical harmonic oscillator. Any calculus text should offer a treatment of a second-order ODE with constant coefficients. See http://tutorial.math.lamar.edu/ for free online calculus resources. The free course http://ocw.mit.edu/courses/mathematics/18-03-differential-equations-spring-2010/ also offers a thorough introduction to differential equations.

$\endgroup$
1
$\begingroup$

If you don't understand the other method, this is how you would do in the realm of real numbers :

Write $$\frac{d^2\theta}{dt^2}=\frac{d\omega}{dt}=\omega\frac{d\omega}{d\theta}$$

I have used that $\omega=\frac{d\theta}{dt}$ in the last step. Now your equation is first order and you can solve it easily.

$$\omega d \omega=-k^2 \theta d\theta$$

You can take from here I guess.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.